(untitled) (Revista LIDER, 2020)
The production of scientific knowledge in the domain boundary, as often happens with social and environmental issues, is accountable by complex epistemological, cultural, political and of scientific knowledge and its relation to defined theories and methodologies in studies of interconnected social and natural phenomena. Semantic systems also influence the hermeneutic processes of science. We also present some questions about the factors that define the social construction of environmental problems, rules and language games in the disputes of senses. Finally, six conditions that coexist with the current situation of science in transit are analyzed in order to further explore the complex environmental phenomena.